Effect of Inoculation Time for Indigenous Probiotic Bacteria Lactobacillus plantarum DAD-13 on the Physiochemical and Organoleptic Properties of Yoghurt Drink: Pengaruh Waktu Inokulasi Bakteri Probiotik Indigenous Lactobacillus plantarum DAD-13 terhadap Sifat Fisikokimia dan Organoleptik Yoghurt Drink - Komalasari, Husnita; Karni, Ine; Heldiyanti, Rina; Arianto, Ahmad Rudi; Rahayu, Endang Sutriswati (Universitas Slamet Riyadi Surakarta, 2024)
Yoghurt drink is a product obtained from fermentation of milk by certain lactic acid bacteria. The aim of this research was to determine how the inoculation time of the indigenous probiotic bacteria Lactobacillus plantarum Dad-13 influences the physicochemical and organoleptic properties of functional plain yoghurt probiotic drink products. This research used an experimental method with a completely randomized design with a single factor, 4 treatments and 3 replications. Reaserch data were analyzed using diversity analysis and Duncan's multiple distance test at a significance level of 5% using SPSS and Minitab 17 software. The results showed that the use of probiotic bacteria significantly affected on viscosity, color L*, color a*, color b*, °HUE, pH, total dissolved solid, and fat content, but did not significantly influenced on protein content. The use of probiotics as a starter in yoghurt drinks increased viscosity, color brightness, pH and fat content, and have a lower total dissolved solid. The best treatment in this study was joint-inoculation who had viscosity 290,67 mPa.s; color L* 89,46; color a* 2,92; color b* 1,61; °HUE 29,47; pH 5,00; total dissolved solid 16,67 °brix; fat content 2,34 %; and protein content 4,12%. For the scoring test, this treatment has a non-sour taste; the aroma is slightly sour; Slightly thick texture and homogeneous consistency. Meanwhile, the hedonic test has a neutral taste, aroma and texture as well as a color, appearance and consistency were quite liked by the panelists.